E-activity management system (administration) for Faculty of Computer and Mathematical Sciences (FSKM) / Noor Fazilah Azlan - Azlan, Noor Fazilah (2013)
There are many systems and application has been migrated to the web-based in world nowadays. Up to now, Faculty of Computer and Mathematical Sciences (FSKM) is still using manual system in order to manage application by student to organize their club’s activity. This project is mainly to help the administrator of FSKM to handle those applications systematically by using this web based application. This is including sending the notification via email to the applicant to inform about the application. The approval will be made by the administrator after considered about budget, transportation and others. Advisors of the clubs in FSKM also will have advantage through this system since they can easily check the application made by the club’s representative. E-activity management system is hopefully will replace the manual system and students will be able to make application by online. With this project, all of application can be easily manage, save time and systematic compare to the old approach.